Analisis Strategi Layanan Perpustakaan untuk Peningkatan Kepuasan Pemustaka di Universitas Islam Negeri Sumatera Utara - Abidah Vitadiani Hutagalung; Nadelia Syahriani; Nesi Dwi Hafsari; Nadya Trihafsari Nasution; Salsabila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Providing satisfactory service is one of the philosophies of a library. The purpose of this study was to determine student expectations and strategies for improving the quality of service at the State Islamic University of North Sumatra Library. In this study, data obtained from the recapitulation of results were processed using SPSS. The results showed that 60% were satisfied with the strategy used to increase user satisfaction, including providing a neat and clean reading room, well-organized books, and a large collection.